Saberes y prácticas con relación al cuidado de la salud en personas con Hipertensión Arterial de la comunidad indígena YANACONA de San Sebastián- Cauca (2021)
In all societies there are different views on health, disease and how to treat it, and more so in an indigenous community, therefore, a model western medical doctor can generate different controversies, especially in places where different cultures coexist, for this reason the health models must be able to respond to the biological, cultural and social diversity of all members of a society, to facilitate equitable and respectful relationships knowing and understanding the sociocultural processes for a society intercultural. Arterial Hypertension (HTN) is a public health problem very prevalent in the Colombian population, in the indigenous community Yanacona of San Sebastián Cauca, a prevalence of 19.79% was found in the year 2017. The objective of this project was to identify the knowledge and practices that are have about health care in people with high blood pressure the Yanacona indigenous community of San Sebastián Cauca. Study methodology qualitative descriptive, and was transmitted as a data collection instrument a semi-structured interview.